When the goddess wakes - Jones, Howard A. (Jones, Howard A. Ring-sworn trilogy., 2021)
"In When the Goddess Wakes, the final book of the Ring-Sworn trilogy, Howard Andrew Jones returns to the five realms of the Dendressi to conclude his heroic, adventure-filled epic fantasy trilogy. The Naor hordes have been driven from the walls, but the Dendressi forces are scattered and fragmented, and their gravest threat lies before them. For their queen has slain the ruling council and fled with the magical artifacts known as the hearthstones, and she is only a few days from turning them to her mad ends. The Altenerai corps has suffered grievous casualties, and Elenai's hearthstone and her source of sorcerous power has been shattered. She and her friends have no choice but to join with the most unlikely of allies. Their goal: to find the queen's hiding place and somehow stop her before she wakes the goddess who will destroy them all... Praised for his ability to write modern epic fantasy that engrosses and entertains, Howard Andrews Jones delivers a finale to his trilogy that reveals the dark secrets and resolves the mysteries and conflicts introduced in the first two books of this series"--